Clinicopathological Study of Kimura disease and Angiolymphoid hyperplasia with eosinophilia in patients at Maharaj Nakorn Chiang Mai Hospital - Chowsilpa, Sayanan; Mahanupab, Pongsak (Biomedical Sciences and Clinical Medicine, 2017)
Objective To evaluate clinicopathologic differences between Kimura disease (KD) and angiolymphoid hyperplasia with eosinophilia (ALHE) Methods Clinical data and pathological slides of KD and ALHE patients at Maharaj Nakorn Chiang Mai Hospital from 1999 through 2011 were retrieved and analyzed. Results A total of 32 KD patients (21 males; 11 females) age 2-74 years (mean 36.44) presented with a painless mass (size 0.4-10 cm; mean 3.75) in the head and neck region had been treated during the study period. The masses had been present for between 1 and 228 months (mean 28.27). There were also 19 ALHE patients (13 males; 6 females) age 1-66 years (mean 32), most of whom had a fi rm, painless mass (n=14) measuring 0.2-3 cm (mean 1.09). Of the ALHE cases, one had a cystic lesion, 2 had indurated skin and 2 had nasal obstruction. Duration of symptoms in the ALHE patients ranged from 1 to 36 months (mean 8.63). Presentation with a painless mass was a signi fi cant clinical diagnostic for KD (p =0.005). Differences in histologic fi ndings between KD and ALHE included the presence of lymphoid follicles in KD (p <0.000) and the extension of KD into deep subcutaneous tissue, salivary glands and skeletal muscle (p =0.029). Conclusions KD was found in female and middle-aged patients, not just young males as previously reported. Conditions which would indicate the presence of KD rather than ALHE include presentation with a mass, pathologic fi ndings of lymphoid follicles and extension into the deep subcutaneous tissue, skeletal muscle and salivary gland.